Z kart dziejów bydgoskiej oświaty 1830/1945-2008 (Kronika Bydgoska, 2012)
The genesis of education in Bydgoszcz, including Polish and German, springs from the operation of schools in the Middle Ages. After 1466, parish schools still played the main role; municipal and monastic, especially Jesuit, schools existed as well. Public people’s schools educated pupils in the elementary rangę. The schools in Bydgoszcz were of multidenominational character. In the period of the partitions of Poland, the operation of education developed in accordance with the policy of the German authorities. It is assumed that the oldest elementary school in Bydgoszcz, within the city limits until the year 1918, was the school established in 1830 in the building in 82 Dworcowa Street. Polish education in Bydgoszcz derived models from rich and extensive traditions - traditions of the Polish independent ideas and traditions of independent operations, organie work traditions, and social activist traditions - dating back to the 19,h century, the epoch of national captivity and collective resistance against the partitioners. The years 1945-1989 in Bydgoszcz in the period of the Polish People’s Republic are issues of education reconstruction, formation of the school authorities and administration, as well as reconstruction and development of education in a communist State. The history of education in Bydgoszcz is not sufficiently compiled, and it reąuires a comprehensive monographic, and later synthetic study. The changing networks and districts of schools from their establishment to the year 1989 need to be researched. During political transformations in Poland after the year 1989, education organisation and structure were changed completely. The transformations forced the necessity to adapt the education system to the new conditions and needs of the democratic State. Besides State schools, later self-govemment schools called public, many different non-public, social and private schools and education institutions were established. Numerous education associations, associations for the managerial personnel, were established and they started to run non-public schools and institutions. This article is a contribution to the history of education in Bydgoszcz illustrated with an example of two typical public schools: Primary School No. 29 and Middle School No. 3 in Bydgoszcz, functioning in the Bydgoszcz self-govemment education system. The education operation of both schools in Bydgoszcz is presented here as an example of the didactic-educational process of self-govemment schools in Bydgoszcz, with an emphasis that each school is different, has its own tradition, and is active in different communities and districts of the city.